2023
DOI: 10.1038/s41598-023-35688-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genetic diversity analysis of high-yielding charcoal rot resistant soybean genotypes

Abstract: Charcoal rot disease caused by Macrophomina phaseolina (Tassi) Goid is one of the most devastating diseases in soybean in India. During 2018, 226 diverse soybean genotypes were evaluated for genetic resistance under hot-spot conditions. Out of them, a subset of 151 genotypes were selected based on Percent Disease Incidence (PDI) and better agronomic performance. Out of these 151 genotypes evaluated during 2019, 43 genotypes were selected based on PDI and superior agronomic performance for further field evaluat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…According to the results, we found that the selection based on MGIDI provided satisfactory gain. The measured MGIDI, based on the BLUP data from multiple traits in two years, selected 20 resistant genotypes (17,80,111,127,81,38,37,61,132,59,Dorfak,58,46,141,18A,54,27,140,51,and 32) that highly overlapped with selected genotypes using cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results, we found that the selection based on MGIDI provided satisfactory gain. The measured MGIDI, based on the BLUP data from multiple traits in two years, selected 20 resistant genotypes (17,80,111,127,81,38,37,61,132,59,Dorfak,58,46,141,18A,54,27,140,51,and 32) that highly overlapped with selected genotypes using cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase the availability of superior seeds, various efforts have been made in the seed sector, including by releasing new superior varieties, both locally and nationally, as a result of plant breeding (Habtegebriel and Abebe, 2023;Sherafatizangeneh et al, 2022;Ali et al, 2022). There are more than 70 soybean varieties that have been released and disseminated to farmers, but it is necessary to study the level of adaptation and stability in various agro-ecosystems such as irrigated paddy fields, rain-fed paddy fields and land so that varieties with high yields are known in these agro-systems (Amrate et al, 2023;Farhud and Mojahed, 2022). New superior varieties can be produced, among others, through purification/ bleaching from local varieties that have long been known and favored by farmers.…”
Section: Methodsmentioning
confidence: 99%
“…Soybean can be planted earlier in warm winter areas. Soybeans grow best where the average daily temperature is 21 0 C (Amrate et al, 2023;Asadipour et al, 2005;Mojahed et al, 2022). It is better to plant soybeans in full sun.…”
Section: Introductionmentioning
confidence: 99%
“…In this, charcoal rot caused by a necrotrophic soil-borne fungus Macrophomina phaseolina (Tassi) Goid is a devastating disease of soybean responsible for significant Distribution of Charcoal Rot of Soybean, its Influencing Factors and Pathogenic Variabilities in Different Regions of Madhya Pradesh yield reduction in the top eight soybean-producing nations (Wrather et al, 2010;Amrate et al, 2023c). It occurs yearly and affects most genotypes, varieties and advanced soybean lines under Madhya Pradesh agro conditions (Amrate et al, 2019;Amrate et al, 2023c). Sudden wilting of plants and greyish-black appearance of lower stems and roots are common symptoms of charcoal rot (Gupta et al, 2012;Amrate et al, 2020b;Sagarika et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Sudden wilting of plants and greyish-black appearance of lower stems and roots are common symptoms of charcoal rot (Gupta et al, 2012;Amrate et al, 2020b;Sagarika et al, 2023). Macrophomina phaseolina has a wide host range (about 500), including field crops, vegetables, fruit, ornamental, medicinal and forest plants (Marquez et al, 2021;Amrate et al, 2023c). Charcoal rot is challenging to manage due to its complex pathogenesis and sudden onset of wilting symptoms (Sagarika et al, 2023;Singh et al, 2024).…”
Section: Introductionmentioning
confidence: 99%